Measurement, modeling and validation of skid resistance of asphalt concrete pavement: Laboratory to field literature review - Kumar A.; Gupta A.; Anupam K. (My University, 2025)
Present article reviews the early and recent developments in skid resistance measurement techniques at asphalt concrete pavement. Suitability and limitations of various methods used for capturing skid characteristics of the surface has been outlined. The harmonization of laboratory and field-testing methods has been summarized briefly. Harmonization is agreement of test outcomes reported from field as well as laboratory. Correlation analysis of various in-situ and laboratory test data has been made to maintain the better harmony of measurement either in field or in laboratory. Measurement of skid resistance in field is time consuming, labor intensive and requires use of costly, advanced and sophisticated instruments. Lab measurement lags in accuracy and still needs improvement in design and working methodology which compelled researchers for looking into modelling as an alternative option. In the subsequent sections, progress in modelling approach (analytical to numerical) has been discussed in brief. Analytical and numerical solutions of asphalt concrete pavement for modelling skid resistance have been reviewed and emphasis for choosing a particular solution has been justified on the basis of accuracy as well as efficacy of the output model. Critical factors affecting skid resistance model like hydroplaning, tire related parameters, temperature, surface texture has been highlighted in this manuscript. Skid data obtained from any model whether it is analytical or numerical, needs to be validated against field measurement or some established data. Validation of skid resistance model using field test and experimentally derived equations in various research studies has been summarized in later section of this article. Few key research directions have been suggested as scope of future study so as to predict a more reliable skid resistance model (1) For predicting dynamic frictional properties with higher accuracy at tire pavement interface, tire pavement interaction modelling still needs improvement considering all field constraints (2) Influence of surface texture, hydroplaning, temperature and pavement ageing needs to be studied in depth for modelling skid resistance as these are critical parameters & contributes significantly. © 2022 the Author(s).